Anticipating Cybersecurity on Artificial Intelligence - Thandy Simanjuntak (Geviva Edukasi Trans Teknologi, 2023)
As artificial intelligence (AI) continues to revolutionize various sectors, the intersection of AI and cybersecurity has emerged as a critical frontier. This paper delves into the realm of